Financial Performance of Sustainable Farmers Cooperative (Koptan) in Bali: Leadership, Organizational Culture, Participation, Budget and TQM - Ni Nyoman Juli Nuryani; Wayan Windia; Ketut Budi Susrusa; I Ketut Suamba (International Journal of Agriculture System, 2016)
This paper deals with financial performance of Koptan include leadership,participation budget, organizational culture and total quality management (TQM). Theresearch objective is to determine the effect of non financial factors on financial performanceKoptan. The study was conducted in Bali, with a focus on Koptan business by consideringthat the business activity is the driving force in the agribusiness sector of the economy. Thedevelopment of this sector will boost the economy of the community so as to create Koptansustainability. Samples are 11 Koptan, with the number of respondents of 97 people. Dataanalysis technique used PLS. The results of this study indicate that, leadership, participation,budget and organizational culture positive and significant impact on TQM Koptan, withthe R-square of 0.63. The effect of leadership, participation, budget and organizationalculture positive and significant impact on the financial performance of Koptan, where asTQM positive and significant impact on the financial performance. It can be concluded that,firstly; leadership, participation budgets, organizational culture and total quality management(TQM) positive and significant impact on the financial performance. Secondly, leadership,participation budgets and organizational culture positive and significant impact on totalquality management (TQM) of Koptan in the region.